A csemegekukorica párolgásdinamikájának vizsgálata Thornthwaite-Mather féle kompenzációs evapotranszspirométerben - Ariel, Tóth; Soós, Gábor; Simon, Szabina; Simon-Gáspár, Brigitta (Acta Agraria Kaposváriensis, 2022)
According to the data provision of the National Meteorological Service, since the early 1980’s an intense warming has begun and it is also reflected in domestic observations. In Hungary, just as in other Central European countries, the extremes of weather events are becoming more common. As a main crop, maize (sweet corn) has an outstanding national and global significance. Certainly, global warming and changes in water supply will harmfully affect the cultivability of maize too. Water stress reduces the leaf surface, therefore because of the less captured photosyntetically active radiation, biomass production and yields will be reduced. Weeds with a wider tolerance range than crops may also become increasingly dangerous competitors in field crop production because of their wide tolerance range, fertility and strong adaptability to changing climate- and precipitation conditions. In this research the effect of climate change on the evapotranspiration of maize was investigated at the Agrometeorological Research Station of MATE Georgikon Campus in Keszthely, between 21 May 2021 and 1 September 2021 in Thornthwaite-Mather type compensation evapotranspirometer. The aim of the study was to assess the main characteristics (like leaf area index, daily evapotranspiration, and yield) of sweetcorn under optimal water supply conditions. Furthermore it was also an aim to determine how weeding affects plant characteristics so half of the treatment (1 vessel of the evapotranspirometer) was kept weed-free, while the other half was exposed to natural weeding. In terms of results, positive relation between temperature and evapotranspiration was found and it has been established, that maximum temperature has a greater effect on evapotranspiration, than daily mean temperature. In case of yield indicators, the negative effect of weeding was statistically detectable and it was also pointed out, that the presence of weeds can negatively affect the quantity of crops. The results of the study was compared to a number of other researches on the subject, and it was concluded that the negative consequences of climate change, especially the increasing frequency of drought-hot periods could pose a major threat to successful maize production in the future.
Keywords: csemegekukorica; evapotranszspiráció; gyomosodás; levélfelület index; klímaváltozás